Permanent broad bed furrow technology for soybean-based cropping systems - Verma, Rakesh Kumar; Nargund, Raghavendra; Singh, K H (Indian Farming, 2024)
Soybean is a leading oilseed crop in India and the world. Currently, national soybean productivity is 1.1 t/ha, compared to world productivity of 2.8 t/ha. Low productivity is mainly attributed to abiotic stresses (drought and flood during the cropping period), biotic stresses (insect pests and diseases), and traditional management practices. Therefore, to counteract abiotic stresses and enhance soybean productivity, a long-term (2017-2023) experiment on Permanent Broad Bed Furrow (PBBF) under soybean-based cropping systems was conducted at the ICAR-Indian Institute of Soybean Research, Indore. Significantly higher yield of kharif and rabi crops, system productivity (27.4%), highest net returns (` 311192/ha), and increased benefit cost ratio (4.53) were observed under PBBF + residue (R) retention as compared to conventional tillage as per farmer’s practices. Similarly, among cropping systems, soybean-potato-late sown wheat reported the highest system productivity (11.5 t/ha), net returns (` 418841/ha), and B: C ratio (4.28). Theavailable nutrients, soil organic carbon, and microbial parameters increased under soybean-potatolate wheat under the PBBF + R crop establishment method. Therefore, adopting a soybean-potatolate wheat cropping system under PBBF+R would be more remunerative for farmers in the Malwa region of central India.